Reconstruction of Geological History Based on Stratigraphic Analysis in the Gombong Region, North Serayu Basin - Adam, Ignasius Mahendradewa; Saadjad, A.; Isliko, R.; Umagapi, R. (Jurnal Geologi dan Sumberdaya Mineral, 2025)
In the North Serayu Basin, there are deepsea sedimentary material and volcanic material are deposited in the terrestrial environment. The varied depositional environments require a detailed geological understanding. Because research has yet to be carried out regarding the reconstruction of the geological history in the Gombong area, this research was carried out to study and understand the chronology of deposition and the condition of its geological structure. Research methods include field observation, stratigraphic analysis, and surface geological structure analysis. From old to young, the stratigraphy of the research area is the Shale Interbedded Unit with Rambatan Sandstone, the Halang Tuff Unit, the Dacite Intrusion Unit, and the Slamet Basalt Lava Unit. The reconstruction of the geological history of the research area began in the Middle Miocene - Late Miocene with the deposition of the Shale Interbedded Unit with Rambatan Sandstone in the lower Bathyal-Abysal bathymetric environment (500-2000 m) and the Halang Tuff Unit was deposited in the Late Miocene-Pliocene-finger conformity. Then, during the Late Miocene, the deposition of the Dacite Intrusion Unit occurred, which had an unconformable relationship (nonconformity) with interbedded shale units with Rambatan Sandstone below. Then, in the Late Miocene - Pliocene, due to the compressional regime phase of the Java Island subduction, a geological structure was formed with the principal stress (σ1) trending relatively northwest- southeast, which resulted in the Sarawak right-slip fault, the Mendelem thrust fault and the Gunungtiga normal fault. Furthermore, during the Pleistocene, volcanic activity continued, producing the Slamet Basalt Lava Unit, which had an incongruent relationship (nonconformity) with the Dacite Intrusion Unit below it. Keywords: Geological History, Stratigraphy, North Serayu Basin.